Analisis Efektivitas Penagihan Pajak Melalui Surat Teguran, Surat Paksa, Dan Penyitaan Untuk Meningkatkan Penerimaan Pajak Penghasilan - Sitepu, Putri Lolita; Wage, Sunarto (Bongaya Journal of Research in Accounting (BJRA), 2023)
The realization of receipt of warning letters, coercion letters and confiscation letters in Batam City has not yet reached 100%, this non-realization may be caused by the ineffective collection through warning letters, coercion and confiscation. The purpose of this study was to see whether letters of reprimand, coercion and tax confiscation were effective in increasing income tax revenue at KPP Pratama Batam Selatan. This type of research is a quantitative descriptive using data in the form of numbers for analysis through the formula of treatment effectiveness. The data source for this research is secondary data obtained from KPP Pratama South Batam. Collecting data researchers using shooting techniques. The sample used to measure the effectiveness of the ratio in this study is income tax arrears issued by forced letters and disbursement of income tax arrears from collection activities by forced letters. The results of the study partially show that the average value of the effectiveness of a coercion letter is 92%, it is included in the effective category, the average value of the effectiveness of a coercion letter is 91%, it is included in the effective category, the average value of the effectiveness of a confiscation letter is 91%, so into the effective category. Simultaneously an average value of 91% is obtained with effective criteria. In conclusion, an effective warning letter to increase income tax receipts at KPP Pratama South Batam or H1 is received, an effective coercion letter to increase income tax receipts at KPP Pratama South Batam or H2 is received, an effective confiscation letter to increase income tax receipts at KPP Pratama South Batam or H3 received, letters of reprimand, letters of coercion and effective confiscation letters to increase income tax receipts at KPP Pratama Batam Selatan or H4 are received